Na’hjeNing’e’s Rivers Indigenous Maps, Diplomacy, and the Writing of Ioway Space (Altre Modernità, 2019)
This essay examines an indigenous map (1837) of the Missouri andMississippi river valleys, which offers an alternative to the territorial mappings of USempire in the era of Indian removal. The map was presented by the Ioway delegateNa’hje Ning’e during an intertribal treaty council in Washington in 1837 and depictsthe Ioway Nation’s historical occupation of large areas in the Mississippi River Valley.Although the American treaty commissioners ultimately dismissed the map's historicalargument and the Ioway's claims, its visual presentation of rivers and indigenousmigrations routes marked an alternative to US territorial mappings of Indian country.Understanding the Mississippi River Valley as a site of territorial contestation,Na’hjeNing’e’s visual rhetoric took Ioway migrations along these waterways seriouslyas a basis for indigenous land claims and sovereignty, presenting an alternative to thesettler state’s mappings of Native space. At the same time, the imbalance of powerrelations within American bureaucratic networks meant that the map is an example ofdisrespected literature: a form of indigenous writing that was legible within colonialsettings, but nevertheless disregarded because it did not align with settler-colonialprojects of indigenous dispossession. By considering the diplomatic calculationsbehind it, this essay argues that Na’hjeNing’e’s map asserted a representation of Iowaysovereignty, but also reveals the bounds on that sovereignty at a moment whenremoval policy and settler expansion profoundly reshaped the social and politicalplace of Indian nations in North America.
Keywords: Native American; cartography; Indian diplomacy; settler colonialism; indigenous sovereignty; Ioway history